(untitled) (Islamic Sciences Journal, 2023)
This research aims to shed light on an important aspect of the Book of Money for Dawoodi (401 AH / 1011 CE), which is the tribute and abscess, which means the financial aspect, particularly during the era of Islam as it represents the main financial revenue of the new state, it is represented by economic and political aspects through imposing state authority and applying the law to the open areas and supporting the Muslims ’money house with funds for managing the affairs of the state and society The research also deals with part of the biography of the author and the era in which he lived if Al-Dawoudi is considered one of the great jurists of his era which is full of sedition and turmoil, but despite these conditions he was able to establish a special line for himself. Which included the, the subject of research, which touched in part on the economy and imports of the Islamic Arab country.